99.8k views
2 votes
Evaluate 7P6 − 2(6C2)

User Ilona
by
5.6k points

2 Answers

7 votes
Multiply 6 by -2 to get -12

7x6-12y2
User Lissie
by
6.1k points
0 votes

The given expression is
^7P_6-2(^6C_2)

Here P represents Permutation and C represents Combination

Thus, the given expression can be rewritten as:


^7P_6-2(^6C_2)=(7!)/((7-6)!)-2(6!)/((6-2)!2!) =(7!)/(1!)-2(6!)/(4!2!)


\therefore ^7P_6-2(^6C_2)=7!-(2* 6* 5* 4!)/(4!* 2)=5040-30=5010

Therefore, for the given expression
^7P_6-2(^6C_2), it's value is 5010


User J Kluseczka
by
5.8k points